Cognitive Task Analysis Methods in Envisioned Tactical Command Decision Making. (November 2019) - McGeorge, Nicolette M.; Kane, Stephanie; Muller, Chris
The battlespace is a volatile and complex environment in which tactical commanders face cognitively challenging responsibilities, compounded with the increased complexity of emerging cyber warfare. It is critical that tactical commanders gain adequate situation awareness for effective decision making to achieve mission success. While current tools enable distribution of large quantities and types of information, they do not adequately support the underlying cognitive work and information needs of tactical commanders. We performed a domain analysis using Cognitive Task Analysis methods, developing a prototypical operational scenario representative of current and envisioned environments, centered on a cyber-attack. Using this analysis, we identified cognitive and information requirements for information displays that support effective tactical decision making. Tactical commanders need to understand dynamic situations in the field, understand the viable courses of actions, know how their mission fits into the larger mission, and communicate with their company subordinates and higher echelons of command.